Drosophila stem cells - Buszczak, Michael (Henry Stewart Talks, 2008)
Lineage tracing, Stem cell niches, Germline stem cell niche in ovary, Germline stem cell niche in testis, Dedifferentiation, Stem cell signaling back to the niche, Intestinal stem cells, Stem cell chromatin